2013
DOI: 10.5603/kp.2013.0195
|View full text |Cite
|
Sign up to set email alerts
|

Is mean platelet volume associated with the angiographic severity of coronary artery disease?

Abstract: We determined a positive correlation between MPV and Gensini and SYNTAX scores. Therefore, this simple haematology test can be used in determining cardiovascular disease burden besides other risk factors during routine clinical practice. For further information about this topic, large-scale studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 26 publications
2
31
1
1
Order By: Relevance
“…Patients with higher MPV levels had high GS and had more severe and critical lesions concurrently. Additionally, a correlation ( p = 0.010) between platelet count and the severity of CAD was observed in this study, in contrast to previous studies [29,30]. The relationship between elevated MPV, platelet counts and the severity of atherosclerosis might be explained by the increase in the metabolic and enzymatic activation of platelets and the increased secretion of mediators from the hemostatically active and larger platelets.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with higher MPV levels had high GS and had more severe and critical lesions concurrently. Additionally, a correlation ( p = 0.010) between platelet count and the severity of CAD was observed in this study, in contrast to previous studies [29,30]. The relationship between elevated MPV, platelet counts and the severity of atherosclerosis might be explained by the increase in the metabolic and enzymatic activation of platelets and the increased secretion of mediators from the hemostatically active and larger platelets.…”
Section: Discussioncontrasting
confidence: 99%
“…MPV is one of the most commonly used hematology tests that measures the size of platelets. A higher MPV is a risk factor for CVD, besides other risk factors [11]. MPV can also be used in determining the severity of CAD and is associated with adverse cardiovascular outcomes in patients with CVD [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The Gensini score was correlated with age, time on dialysis (both p < 0.001), NLR (p = 0.004), and C-reactive protein levels (p = 0.034) and inversely correlated with left ventricular ejection fraction (p = 0.023). Multivariate regression analysis showed that age (p = 0.001), time on dialysis 1 3 which can be derived from the complete blood count, have been studied as novel markers of the presence and severity of coronary artery disease (CAD) [8][9][10][11][12][13][14][15]. These markers could help to estimate the prognosis of CAD in patients with CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Plateletendothelial interactions facilitate the secondary capture of neutrophils and other leukocytes, which stimulates interaction with various immune and endothelial cells (23,24). Elevated MPV reflects increased inflammation in numerous processes, including atherogenesis and sepsis (7,25). In addition, it has been shown that oxidative stress leads to increased MPV levels (26,27).…”
Section: Discussionmentioning
confidence: 99%